Petition from the people of Banji, Bafut Area in Regard to Bafut Criminal Case No. 85 (Colonial Letters and the Contact of Knowledges, 1950)
This file contains colonial letters on petition from the Banji, Bafut Area in regard to Bafut criminal case No. 85
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; Petitions; British Colonisation; Colonial Records; Colonial Intelligence Report; Bafut; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies